2007
DOI: 10.1051/vetres:2007037
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-optimised E2 constructs from BVDV-1b and BVDV-2 for DNA immunisation in cattle

Abstract: -We report DNA immunisation experiments in cattle using plasmid constructs that encoded glycoprotein E2 from bovine viral diarrhoea virus (BVDV)-1 (E2.1) and BVDV-2 (E2.2). The coding sequences were optimised for efficient expression in mammalian cells. A modified leader peptide sequence from protein gD of BoHV1 was inserted upstream of the E2 coding sequences for efficient membrane export of the proteins. Recombinant E2 were efficiently expressed in COS7 cells and they presented the native viral epitopes as j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The selection of E2 and NS3 proteins as antigen targets for a BVDV vaccine has been established previously. Our own studies and that of others tested the efficacy of E2-based vaccines and showed an encouraging level of partial protection from BVDV challenge [6,20,[24][25][26][27][28][29]. Vaccination of cattle with the DNA vaccine expressing the highly immunogenic E2 induces protective immunity [6].…”
Section: Discussionmentioning
confidence: 72%
“…The selection of E2 and NS3 proteins as antigen targets for a BVDV vaccine has been established previously. Our own studies and that of others tested the efficacy of E2-based vaccines and showed an encouraging level of partial protection from BVDV challenge [6,20,[24][25][26][27][28][29]. Vaccination of cattle with the DNA vaccine expressing the highly immunogenic E2 induces protective immunity [6].…”
Section: Discussionmentioning
confidence: 72%
“…The E2 protein is the most abundant surface protein of BVDV and contains the major BVDV-neutralizing antigenic site. It has been extensively utilized in the development of BVDV vaccines to induce BVDV-neutralizing antibodies ( 151 , 152 ). The novel MHC-II-targeted BVDV subunit vaccine has shown a rapid and sustained neutralizing antibody response in cattle compared to conventional vaccines ( 153 ).…”
Section: The Current Status Of Research On Major Bovine Vaccinesmentioning
confidence: 99%